The Urgency of Maqasid Shariah in Combating Religious Extremism from Ibn Ashur's Perspective - Mukhtar*, Muh. Riezky Pradana; Asmuni, Asmuni (Universitas Syiah Kuala, 2024)
Religious extremism has become a prominent issue widely discussed worldwide today. Numerous studies from various perspectives have been conducted by scholars from both the Western and Eastern traditions to understand and identify solutions to the problem. Although the issue of religious extremism is considered somewhat sensitive due to its subjective classification, sometimes based on the biases of the evaluators, the Islamic perspective on progressive fiqh issues needs to be analyzed and highlighted as one of the efforts to address the phenomenon of extremism. This aims to prevent greater harm to the Muslim community and, consequently, preserve religion, life, intellect, honor, and wealth as desired by Islamic law (maqasid Sharia). This article employs a qualitative approach using a descriptive-analytical method, which seeks to critically describe the substance of various concepts and theories related to the moderate concept according to Ibn Ashur. The primary data sources are Ibn Ashur's written works discussing the Maqasid Sharia. Additionally, literature related to religious extremism will be utilized. This article is expected to contribute to the understanding and handling of religious extremism by integrating the principles of Maqasid Sharia from Ibn Ashur's perspective. The purpose of this article is to identify and analyze the significance of Maqasid Sharia in the context of combating religious extremism based on Ibn Ashur's perspective. It also aims to provide new insights into efforts to combat religious extremism by detailing the importance of Maqasid Sharia according to Ibn Ashur's thoughts.